T - 76 = 0
If you switch it around, it becomes:
0 + 76 = t
0 + 76 = 76
t = 76
~Hope this helped~
Answer:
Pleaseee post the question clearly
Thus L.H.S = R.H.S that is 2/√3cosx + sinx = sec(Π/6-x) is proved
We have to prove that
2/√3cosx + sinx = sec(Π/6-x)
To prove this we will solve the right-hand side of the equation which is
R.H.S = sec(Π/6-x)
= 1/cos(Π/6-x)
[As secƟ = 1/cosƟ)
= 1/[cos Π/6cosx + sin Π/6sinx]
[As cos (X-Y) = cosXcosY + sinXsinY , which is a trigonometry identity where X = Π/6 and Y = x]
= 1/[√3/2cosx + 1/2sinx]
= 1/(√3cosx + sinx]/2
= 2/√3cosx + sinx
R.H.S = L.H.S
Hence 2/√3cosx + sinx = sec(Π/6-x) is proved
Learn more about trigonometry here : brainly.com/question/7331447
#SPJ9
Answer:
x=15is your answer
Step-by-step explanation:
8x=120 vertically opposite angle
x=120/8=15
for question 1
Area of Base B =45×25 = 1125 cm²
perimeter of base P = 2(45+25) = 140 cm
Height = 15 cm
Using the formula
Surface area = 2B + Ph
A = 2×1125 + 140×15= 4350 cm²
Voume = Bh = 1125×15= 16875 cm³
For question 2,
Area of base = 7× 5/2= 17.5 cm²
Perimeter of base = (7+7+7) = 21 cm
Surface area = 2B + Ph
Surface area of prism = 2×17.5+ 21×10 = 245cm²
Volume = Bh = 17.5×10 = 175 cm³